2015
DOI: 10.1080/19336896.2015.1118602
|View full text |Cite
|
Sign up to set email alerts
|

The prion-ZIP connection: From cousins to partners in iron uptake

Abstract: Converging observations from disparate lines of inquiry are beginning to clarify the cause of brain iron dyshomeostasis in sporadic Creutzfeldt-Jakob disease (sCJD), a neurodegenerative condition associated with the conversion of prion protein (PrPC), a plasma membrane glycoprotein, from α-helical to a β-sheet rich PrP-scrapie (PrPSc) isoform. Biochemical evidence indicates that PrPC facilitates cellular iron uptake by functioning as a membrane-bound ferrireductase (FR), an activity necessary for the transport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Other than copper and manganese ions, zinc and iron ions are also essential metal ions in humans. In terms of iron, PrP C are considered to modulate iron homeostasis with the Zrt, Irt-like protein (ZIP) family [ 39 ], but the role of iron in the inflammation associated with prion disease is ambiguous. In regards to zinc, there are many studies focusing on zinc as an antagonist with copper [ 40 ], and PrP C can induce the uptake of zinc in neurons [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other than copper and manganese ions, zinc and iron ions are also essential metal ions in humans. In terms of iron, PrP C are considered to modulate iron homeostasis with the Zrt, Irt-like protein (ZIP) family [ 39 ], but the role of iron in the inflammation associated with prion disease is ambiguous. In regards to zinc, there are many studies focusing on zinc as an antagonist with copper [ 40 ], and PrP C can induce the uptake of zinc in neurons [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent studies have shown that the prion protein (PrP), mutations of which causes prion disease, is also involved in transporting NTBI, at least in the liver, kidney, and neuroblastoma cells, by acting as a ferrireductase partner for ZIP14 and DMT1. 7073 As discussed later in this review, α-synuclein, mutations of which cause Parkinson’s disease, also possesses ferrireductase activity and promotes Fe 2+ influx. 7477…”
Section: Brain Iron Transportmentioning
confidence: 97%
“…A ferrireductase-deficient mutant of PrP (PrPΔ51–89) lacked this activity [ 66 ], suggesting that PrP C promotes the retrieval of iron via its ferrireductase activity. Additional research unveiled the mechanism of such PrP C modulation of kidney iron metabolism: a cellular prion protein acts as a ferrireductase partner and regulator for divalent metal iron transporters ZIP14 and DMT1 [ 109 , 110 ].…”
Section: Physiological Functions Of Prp C In the Kidneysmentioning
confidence: 99%